Intervensi Pemberdayaan Berbasis Keluarga terhadap Peningkatan Perilaku Perawatan Diri Pasien dengan Diabetes Mellitus Tipe 2 - Rianti Pramita; Siti Saidah Nasution; Jenny Marlindawani Purba (Journal of Telenursing (JOTING), 2021)
This study aims to identify the effect of family empowerment intervention on the self-care of patients with type 2 diabetes mellitus. The research method used was quantitative with a Quasy Experimental Non-Equivalent Control Group Pretest-Postest Design. Respondents in this study were patients with type 2 diabetes mellitus totaling 70 respondents. Data were collected using the Summary of Diabetes Self Care Activities (SDSCA) questionnaire consisting of 14 question items. Data were analyzed using parametric tests (paired t-test and t-test for independent groups). The results of this study indicate a difference between the mean value of self-care in the intervention group and the control group after being given treatment with a p-value of 0.001 (t = -19,027; p-value = 0.001). In conclusion, family empowerment intervention affects self-care in DMT2 patients. Keywords: Type 2 Diabetes Mellitus, Family Empowerment, Self Care